Contact and the 2020 Pandemic: A Poetic Autoethnography. Issue 2 (August 2021) - Pelias, Ronald J.
This poetic autoethnography explores aspects of human contact and communication during the COVID-19 pandemic of 2020. Through a series of poems, the inquiry focuses upon the desire for ordinary interactions and the fear of contamination. The piece stands as a lament, not only for those who have died and have become ill from the virus, but also for the loss of human connection as people practice in varying degrees social distancing.